The evolution of the key sectors in the Philippine economy using an AHP-based sector prioritization index - Daryn Joy Go; Michael Angelo Promentilla; Kathleen Aviso; Krista Danielle Yu (Economies, 2019)
Economic sectors play a vital role in ensuring that government's goals are achieved. This study analyzes the evolution of the structure and key sectors of an economy through the use of a sector prioritization index. This methodology integrates input-output analysis and analytic hierarchy process to determine the structural changes experienced by the economy, while accounting for the changes in the government's priorities and concerns over time. Using the case of the Philippines from 1969 to 2012, this study shows a time-series analysis of the transformation that the economy underwent alongside with the government's prioritization mechanism. We found that the manufacturing sector had consistently received high-priority rankings, while the agriculture sector had recently moved from a high- to mid-priority ranking, indicating the country's shift towards a more industry-driven economy. These findings were supported by the private services and trade sectors' high-priority rankings towards the latter half of the time period. Overall, our methodology was able to identify key sectors that reflect the country's economic and political situation across different eras.
Keywords: 330; analytic hierarchy process; economic development; economic evolution; input-output analysis; Philippines; sector interdependence; sector prioritization